Impact of Work Family Conflict on Job and Life Satisfaction for Female Executive MBA Students (Journal of Education and Educational Development, 2021)
Work family conflict is an established phenomenon of modern economies. It becomes more intense for female labour force performing multiple roles in the society. This study was conducted to answer the research questions of impact of Work Family Conflict on Job Satisfaction and affect of job satisfaction on life satisfaction of female executive students who are working as well as studying. Purpose of the study was to identify areas of conflict, for the female students to enhance their qualification as future labour force, and examine the association between Work Family Conflict, Job Satisfaction and Life Satisfaction. The study worked on three hypotheses. The data was collected from a sample of 200 population of executive MBA students during semester from four business universities in Karachi. Questionnaire also included demographic survey questions information regarding age and marital status. The results of the survey reported negative correlation between work family conflict and job and life satisfaction. Family support, value system of traditional societies like Pakistan and individual interpretation of self-reporting method were the reasons ascertained for the results.